Approaches to enthalpy approximation in numerical simulation of two-component alloy solidification - Sczygiol, Norbert (Computer Assisted Methods in Engineering and Science, 2023)
The paper deals with the numerical modelling of solidification of two- component metal alloys. The numerical model was worked out using the enthalpy formulation of solidification and the finite element method. The work concentrated on one enthalpy formulation, namely the basic enthalpy formulation [l1]. The models of solid phase growth as well as implementation details are shown in the paper [8]. A comparison of the results of the numerical simulation of solidification was made for three approaches to enthalpy approximation as a function of temperature. The three approaches were called: complete, incomplete and linear. The results of simulation, for incomplete enthalpy approximation were almost identical to the results of complete approximation. The computing time for incomplete approximation was substantially lower than the computing time for complete approximation, and comparable to the computing time for linear approximation.